2020
DOI: 10.1002/mrm.28503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and quantitative assessment of saturation transfer for water‐based detection of the aliphatic protons in carbohydrate polymers

Abstract: Purpose: CEST MRI experiments of mobile macromolecules, for example, proteins, carbohydrates, and phospholipids, often show signals due to saturation transfer from aliphatic protons to water. Currently, the mechanism of this nuclear Overhauser effect (NOE)-based transfer pathway is not completely understood and could be due either to NOEs directly to bound water or NOEs relayed intramolecularly via exchangeable protons. We used glycogen as a model system to investigate this saturation transfer pathway in sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…(w∕2 residual saturation transfer background signal remained over a broad frequency range even at pH 6 (purple arrow in Figure 2B). As expected for exchange-relayed NOEs and shown previously in phantoms, 59,60 the aliphatic rNOE at the opposite frequency range also demonstrated pH dependence. The Guan effect size first increased when lowering pH from 7.5 to 7, and then it stabilized and decreased with further reduction of pH, which was consistent with previous observations.…”
Section: Phantomssupporting
confidence: 86%
See 1 more Smart Citation
“…(w∕2 residual saturation transfer background signal remained over a broad frequency range even at pH 6 (purple arrow in Figure 2B). As expected for exchange-relayed NOEs and shown previously in phantoms, 59,60 the aliphatic rNOE at the opposite frequency range also demonstrated pH dependence. The Guan effect size first increased when lowering pH from 7.5 to 7, and then it stabilized and decreased with further reduction of pH, which was consistent with previous observations.…”
Section: Phantomssupporting
confidence: 86%
“…In contrast to a recent creatine validation study 45,63 using a knockout mouse model, validation of the amideCEST signal in the brain Z-spectrum cannot be easily achieved by removing the mobile proteins in tissue. However, we could exploit the property that CEST signals from amide and Guan protons are strongly pH-dependent, whereas rNOEs have weak pH dependence and MTC is insensitive to pH 60,64 in the physiological range. As demonstrated by the egg white model system (Figure 2), the amide CEST signal is visible at 3T with a peak around 3.5 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Murase published numerical analyses of the Z‐spectra in the presence of multiple exchanging pools which can be applied to exchange‐relayed NOE 47 . Zhou et al has reported a simplified analytical solution for relayed NOE 33 and showed that the pH‐sensitivity of the rNOE signal is determined by whether k CE is much faster than k NOE . This could lead to a conclusion that the rNOE signal observed in mobile protein would be independent of pH at physiological conditions, because even the slow exchanging amide (30 s −1 ) 10 is about an order of magnitude faster than the NOE transfer rate (2‐3 s −1 ) 30,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have suggested that relayed NOE should be the dominant pathway for mobile proteins 31,32 ; thus, it is generally assumed that relayed NOE applies to in vivo brain CEST studies. A very recent study of glycogen has also suggested that the NOE signal may also be relayed in some carbohydrate macromolecules 19,33 …”
Section: Introductionmentioning
confidence: 99%
“…We observed lower MTR values in symptomatic patients compared with non-symptomatic patients and controls. To fully understand the biophysical origins of MT in Pompe muscle, a more detailed quantitative MT study is warranted that takes into account pool sizes, T1, lipids, and multiple transfer magnetization transfer mechanisms ( 5 , 19 ).…”
Section: Discussionmentioning
confidence: 99%